This Special Education Is Unique For Teachers, Students, Parents, Leaders And Organizations - et. al., Nazrah Binti Jamaludin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Understanding special education is a complex thing. It takes someone to create an alien world filled with its citizens with disabilities. Choosing to be together in the world of special education provides an indicator that preparing oneself to be as special as special education itself. Entering the world of special education, automatically everything needs to be directed to be special and unique. Can we all imagine how stressful and stressful the physical and mental condition of parents who handle their children who are categorized as people with disabilities (OKU)? Do we fantasize about how a teacher controls their class and teaching when faced with the uncertainty of behavior and speech of students with special needs (MBK) in school? Is it worth it if we don’t become as special as possible in the world of special education? This qualitative study was conducted to explore the perceptions of those closest to special education, namely teachers, students, school leadership and parents in stating how unique special education is in their hearts. A total of 20 people were involved in the interview sessions conducted. The results of the interviews were transcribed and analyzed. The findings of this study are expected to provide an overview of the uniqueness of special education to the community and subsequent researchers.